Aflatoxin and protein content in 13 bean (Phaseolus vulgaris L.) varieties - Peña-Betancourt Silvia Denise; Conde-Martínez Víctor (Revista Mexicana de Ciencias Agrícolas, 2018)
In Mexico, the bean (Phaseolus vulgaris L.) is a highly consumed legume seed (11 kg per capita annually), so that its cultivation it ́s quite extensive in different regions. In this study we investigated the presence of aflatoxins in eight common bean varieties and five improved bean varieties, in addition to protein and moisture. In all the varieties tested, the moisture content showed large variations (from 6 to 16%), being 16% of the varieties studied outside the normal (<12%). The highest content of protein was detected in the improved bean varieties (26.1%) and, the lowest in commercial (19.8% ± 3.09) and wild varieties (20.78% ± 1.93). All of them showed af latoxins on average of 7.46 ng g-1 and a range from 5 to 13 ng g-1. The highest level of contamination was observed in the improved bean varieties (9.2 ± 2.9 ng g-1), followed by the commercial ones ± 0.95 7.25 ng g-1 and wild varieties 6 ± 1 ng g-1. Tannins were detected in wild bean varieties at a level of0.44%±0.13.Theresultsobtainedconfirmthepresenceof toxic and anti-nutritional compounds in the different varieties of common and wild beans at levels permitted by national law, but may pose a risk to the consumer ́s health due to its high consumption.